District nurses' experiences with involuntary treatment in dementia care at home: a qualitative descriptive study - Vincent R.A. Moermans; Jan P.H. Hamers; Hilde Verbeek; Bernadette Dierckx de Casterlé; Koen Milisen; Michel H.C. Bleijlevens (BMC, 2023)
Abstract Background Research shows that half of person(s) living with dementia (PLWD) receive care which they resist and/or have not given consent to, defined as involuntary treatment. District nurses play a key role in providing this care. Knowledge about how district nurses experience involuntary treatment is lacking. Therefore, the aim of this study was to describe the experiences of district nurses who used involuntary treatment for PLWD at home. Methods A qualitative descriptive design using semi-structured interviews. Sixteen district nurses with experience in involuntary treatment for PLWD were recruited through purposive sampling. Data were analysed using the Qualitative Analysis Guide of Leuven. Results District nurses' experiences with involuntary treatment were influenced by their involvement in the decision-making process. When they were involved, they considered involuntary treatment use to be appropriate care. However, at the moment that involuntary treatment use was started, district nurses were worried that its use was unjust since they wished to respect the wishes of the PLWD. Eventually, district nurses found, from a professional perspective, that involuntary treatment use was necessary, and that safety outweighed the autonomy of the PLWD. District nurses experienced dealing with this dilemma as stressful, due to conflicting values. If district nurses were not involved in the decision-making process regarding the use of involuntary treatment, family caregivers generally decided on its use. Often, district nurses perceived this request as inappropriate dementia care and they first tried to create a dialogue with the family caregivers to reach a compromise. However, in most cases, family caregivers stood by their request and the district nurse still provided involuntary treatment and found this difficult to tolerate. Conclusions Our results show that district nurses experience involuntary treatment use as stressful due to dealing with obverse values of safety versus autonomy. To prevent involuntary treatment use and obverse values, we need to increase their ethical awareness, communication skills, knowledge and skills with person-centred care so they can deal with situations that can evolve into involuntary treatment use in a person-centred manner.